Productive linkages and employment multipliers for the cattle raising economic activity based on the input-output table of Costa Rica 2012 - Arguedas Villalobos, Silvia (2019)
This paper aims to analyze the relevance of cattle raising economic activity, based on the identification of productive linkages and the generation of direct and total employment that this economic activity creates with other activities. This will be determined based on the input-output table of Costa Rica 2012 through the application of the input-output models studied by Chenery, H.B. and Watanabe, T. (1958), and Hirschman and Rasmussen (1963), cited by Schuschny, A.R. (2005). Among the main results, it is confirmed that the cattle raising economic activity is a key activity for the Costa Rican economy. This because this activity generates important productive linkages though its demand of utilized inputs as intermediate consumption and its production offer, which is utilized by other industries as raw material. Furthermore, in agricultural industry, it is the main activity in terms of generation of indirect and total employment. Nationwide, it is among the top ten economic activities with greater indirect and total employment generation.